On photokinetics under polychromatic light - Maafi, Mounir (Frontiers in Chemistry, 2024)
Since the dawn of photochemistry 150 years ago, photoreactions have been conducted under polychromatic light. However, despite the pivotal role that photokinetics should naturally play for such reactive photosystems, the literature lacks a comprehensive description of that area. Indeed, one fails to identify explicit model integrated rate laws for these reactions, a characteristic type for their kinetic behavior, or their kinetic order. In addition, there is no consensus in the community on standardized investigative tools to evaluate the reactivity of these photosystems, nor are there venues for the discussion of such photokinetic issues. The present work is a contribution addressing some of these knowledge gaps. It proposes an unprecedented general formula capable of mapping out the kinetic traces of photoreactions under polychromatic light irradiation. This article quantitatively discusses several reaction situations, including the effects of initial reactant concentration and the presence of spectator molecules. It also develops a methodology for standardizing actinometers and defines and describes both the spectral range of highest reactivity and the photonic yield. The validity of the model equation has been proven by comparing its results to both theoretical counterparts and those generated by fourth-order Runge–Kutta numerical calculations. For the first time, a confirmation of the Φ-order character of the kinetics under polychromatic light was established.